Rebranding Model of Dairy Cattle Agro Tourism in Malang Indonesia - Putritamara, Jaisy Aghniarahim; Siti Azizah,; Umi Wisapti Ningsih, (Technium Social Sciences Journal, 2020)
This study aims to analyze the rebranding of agro-educational tourism based on dairy cattle. This research uses a qualitative-based explanatory approach from case studies. The research was conducted in the Nusa Pelangi Dairy Cattle Agro Tourism (Bromo Tengger Semeru National Park area) Malang Regency. Data analysis used the Complex Processes Model. The results of the Analysis showed the barriers rebranding more than enablers. Barrier's rebranding of agro-tourism was leadership roles in management, developing stakeholders' understanding of brands, inadequate research on rebranding, branding implementation in internal management, stakeholder coordination, integrated marketing development, and tension stakeholders. Enablers in the agro-tourism rebranding process include the autocratic approach, narrow strategic brand, sustainable inadequate brand attributes, and customer feedback. Barriers were higher than enablers because internal management conditions were not conducive. The majority of employees were family members, so authority and delegation are unclear. The role of the organizational structure was not good. Management and stakeholders didn't have the same vision. So this research strategy was needed to completing internal conflict management in improving cooperative relationships with stakeholders and increase stakeholders in the various lines. So far, stakeholder support has only been from the public sector, so expectations need of stakeholder involvement in the realm of tourism is needed, improvement of the tourism promotion platform, the national charm movement of Indonesia, and Non-Government Organizations (NGOs)